A systematic approach to the development of research-based web design guidelines for older people - Zaphiris, Panayiotis; Kurniawan, Sri Hastuti; Ghiawadwala, Mariya (My University, 2007)
This paper presents a systematic approach to the development of a set of research-based ageing-centred web design guidelines (SilverWeb Guidelines). The approach included an initial extensive literature review in the area of human–computer interaction and ageing, the development of an initial set of guidelines based on the reviewed literature, a card sorting exercise for their classification, an affinity diagramming exercise for the reduction and further finalisation of the guidelines, and finally a set of heuristic evaluations for the validation and test of robustness of the guidelines. The 38 final guidelines are grouped into eleven distinct categories (target design, use of graphics, navigation, browser window features, content layout design, links, user cognitive design, use of colour and background, text design, search engine, user feedback and support).
Keywords: Research-based guidelines; Ageing; Web usability; Acessibility